GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 12620164 species occurrences available in GBIF matching the query: HasGeospatialIssue: false Geometry: POLYGON((19.42 -70.11,19.42 -28.38,129.64 -28.38,129.64 -70.11,19.42 -70.11)). The dataset includes 12620164 records from 998 constituent datasets: 2 records from Phthiraptera. 1100 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 57 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 1 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 338 records from International Barcode of Life project (iBOL). 10 records from Entocytheridae (Ostracoda) World Database. 4409 records from A global database for the distributions of crop wild relatives. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 503 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1076 records from Phanerogamic Botanical Collections (S). 48 records from Mollusca collection of National Museum of Nature and Science. 21 records from African Rodentia. 289 records from MVZ Herp Collection (Arctos). 39273 records from PRECIS (KwaZulu-Natal Herbarium). 4 records from University of Vienna, Institute for Botany - Herbarium WU. 2271 records from SANBI: DNA Banking(1987-2011). 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 31 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 425 records from MVZ Mammal Collection (Arctos). 7364 records from Australian National Wildlife Collection provider for OZCAM. 4536 records from ecoscope_observation_database. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 1203 records from LACM Entomology Collection. 45 records from Orthopteroidea. 2355 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 958 records from Bee Biology and Systematics Laboratory. 1 records from Portuguese Seaweeds. 1 records from Collection of Heteroptera. 318 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 16900 records from AntWeb. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 486 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 134 records from CAS Entomology (ENT). 34 records from Zoology (Museum of Evolution - Uppsala). 5851 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 51 records from PlutoF platform observations. 29 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 4 records from A new species of Fidelia Friese, 1899 (Hymenoptera, Megachilidae), with a key to the species of the genus. 14 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 324373 records from PRECIS. 1844 records from CSIRO Ichthyology provider for OZCAM. 1553 records from Fishbase. 26658 records from Occurrence records of southern African aquatic biodiversity. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 43 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 19 records from New genera, species and records of Maeridae from Australian Waters: Austromaera, Ceradocus, Glossomaera, Hamimaera, Huonella gen. nov., Linguimaera and Maeraceterus gen. nov. (Crustacea: Amphipoda). 195 records from KUBI Mammalogy Collection. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 4 records from New data on the jumping spiders of the subfamily Spartaeinae (Araneae: Salticidae) from Africa. 2 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 27 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 79 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 78 records from The avian collection at the Natural History Museum, Oslo, Norway. 38 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 10620 records from CSIRO, SRFME, Algal Biomass, Perth region, Southwest Australia, 2003-2005. 1582613 records from Southern African Bird Atlas Project. 63 records from (Data S1) Palynology of ODP Site 119-739. 5386 records from IMOS - AusCPR: Phytoplankton Abundance. 6184 records from SA Flora (BDBSA). 6 records from NCSM Fishes Collection. 8 records from Revision of Afrotropical Dyscritobaeus Perkins, 1910 (Hymenoptera: Scelionidae). 58929 records from AM: Freshwater Invertebrates (1900-2005). 2 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 6 records from New Leucettidae de Laubenfels, 1936 (Porifera, Calcarea) from Western Australia. 8 records from Culture Collection of Cryophilic Algae. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 12 records from DMNS Bird Collection (Arctos). 4 records from The Fish Collection at the Zoologische Staatssammlung München. 92382 records from Coordinated Waterbird Counts. 83 records from BioAcoustica: Wildlife Sounds Database. 3 records from Sipuncula collection of National Museum of Nature and Science. 7 records from Coleção de Echinodermata do Museu Nacional - MNRJ-ECHINO. 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 5 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 21 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 186 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 4 records from CUMV Fish Collection (Arctos). 457 records from Field Museum of Natural History (Zoology) Bird Collection. 4558 records from IZIKO: Marine Invertebrate Collection (1900-2011). 3 records from Collection des Mollusques (BOUM). 15954 records from Reef Life Survey: Global reef fish dataset. 51322 records from Museum Victoria provider for OZCAM. 5 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 8 records from Cowan Tetrapod Collection - Mammals. 1 records from MBM - Herbário do Museu Botânico Municipal. 13 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 10 records from Description of the males of Euprosthenops australis Simon, 1898 and Euprosthenopsis pulchella (Pocock, 1902) (Araneae: Pisauridae). 331 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 5 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 8309 records from SA Fauna (BDBSA). 3 records from BMSM Bailey-Matthews National Shell Museum. 234 records from Field Museum of Natural History (Zoology) Mammal Collection. 2 records from MVZ Hildebrand Collection (Arctos). 1 records from Ornithologie ZMK. 24670 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 12 records from Lund Museum of Zoology (MZLU). 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 14 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 5 records from Crustacea ZMK. 75 records from CAS Invertebrate Zoology (IZ). 2867 records from IMOS - AusCPR: Zooplankton Abundance. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 47 records from Tallinn Botanic Garden. 5 records from A review of Lamyra Loew (Diptera: Asilidae: Laphriinae). 51766 records from Historical Bird Atlas. 14 records from UAM Bird Collection (Arctos). 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 1 records from arim. 803636 records from BirdLife Australia, Birdata. 4425 records from Museum of Comparative Zoology, Harvard University. 11 records from Naturalis Biodiversity Center (NL) - Cnidaria. 806611 records from Australia's Virtual Herbarium. 2 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 163 records from Ichthyology Collection - Royal Ontario Museum. 24 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 192 records from CAS Ornithology (ORN). 349888 records from EOD - eBird Observation Dataset. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 433 records from Tasmanian Museum and Art Gallery provider for OZCAM. 2967 records from iNaturalist Research-grade Observations. 1 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 24 records from UCBG TAPIR Provider. 3012 records from CSIRO, Cruise SS200510, Benthic Biodiversity, Western Australia, 2005. 11 records from Global caridean shrimp fauna. 234 records from CONN. 1 records from H.A. Stephens Herbarium. 1355 records from CSIRO, fish surveys by the Soela, 1980s. 2 records from NYSM Birds. 22 records from Recent Invertebrates Specimens. 1209 records from Invertebrates Collection of the Swedish Museum of Natural History. 123 records from KUBI Ichthyology Tissue Collection. 42510 records from AM: Terrestrial Insect Collections (1896-2000). 3394 records from Global Lacustrine Diatoms. 22551 records from SAEON: Historical Research Survey Database (1897-1949). 2 records from University of California Museum of Paleontology. 44395 records from UCT: Southern African Butterfly Conservation Assessment (1815-2009). 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 21 records from Mammals housed at MHNG, Geneva. 23 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr).. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 1 records from mel. 18 records from Estonian University of Life Sciences. 157 records from Essig Museum of Entomology. 394 records from CAS Ichthyology (ICH). 85 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 10817 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 3 records from DMNS Mammal Collection (Arctos). 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 1 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 3 records from TNHC Ichthyology Collection. 10 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 5 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 7 records from New talitrids from South Africa (Amphipoda, Senticaudata, Talitroidea, Talitridae) with notes on their ecology. 7005 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 4 records from NRM-Herpetology. 1 records from Two new species of Dactylonotus Parent, 1934 (Diptera: Dolichopodidae) from South Africa and a key to Afrotropical species. 793 records from Live benthic foraminifera in South Atlantic surface sediments. 358 records from Counting of planktic foraminifera of ODP Hole 182-1129C. 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 1100 records from (Table AT3) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128B. 87 records from Diveboard - Scuba diving citizen science observations. 146 records from Bryophyte herbarium, NTNU University Museum. 7 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe).. 435 records from Illinois Natural History Survey Insect Collection. 51 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1821 records from The Brown University Foraminiferal Data Base (BFD). 4 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 5 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/011-3. 9 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/012-4. 6 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 3 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/038-7. 27 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/041-5. 5 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/042-5. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 14 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/045-9. 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 12 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/048-5. 7 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/049-5. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/061-3. 11 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/088-7. 14 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 12 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/091-3. 12 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6. 15 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/107-6. 12 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 1 records from Colección Ictiológica del CENPAT-CONICET. 1691 records from naturgucker. 2 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 3 records from Redescription and generic placement of the spider Cryptachaea gigantipes (Keyserling, 1890) (Araneae: Theridiidae) and notes on related synanthropic species in Australasia. 798 records from The First Comprehensive Description of the Biodiversity and Biogeography of Antarctic and Sub-Antarctic Intertidal Communities. 1 records from Cleveland Museum of Natural History.. 35 records from Erik Acharius lichen collection. 29 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 21 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/011-3. 15 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/012-5. 18 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/014-4. 15 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/038-3. 14 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 23 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/043-2. 19 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/045-2. 19 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/046-3. 18 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/048-3. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/049-3. 19 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 9 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/088-4. 16 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/090-4. 19 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 21 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/092-3. 24 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/107-5. 21 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/108-1. 1 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 412 records from Occurrence data of Afrotropical Mydidae (Insecta: Diptera: Asiloidea). 84 records from CAS Mammalogy (MAM). 4 records from A new genus and five new species of Astieae (Araneae: Salticidae) from Australia, with remarks on distribution. 75 records from Microzooplankton abundance measured on water bottle samples at station PS58/009-2. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/011-1. 68 records from Microzooplankton abundance measured on water bottle samples at station PS58/012-5. 66 records from Microzooplankton abundance measured on water bottle samples at station PS58/014-4. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 56 records from Microzooplankton abundance measured on water bottle samples at station PS58/041-2. 67 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 69 records from Microzooplankton abundance measured on water bottle samples at station PS58/043-2. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/045-2. 88 records from Microzooplankton abundance measured on water bottle samples at station PS58/046-3. 65 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 69 records from Microzooplankton abundance measured on water bottle samples at station PS58/049-3. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 68 records from Microzooplankton abundance measured on water bottle samples at station PS58/088-4. 63 records from Microzooplankton abundance measured on water bottle samples at station PS58/090-4. 57 records from Microzooplankton abundance measured on water bottle samples at station PS58/091-4. 72 records from Microzooplankton abundance measured on water bottle samples at station PS58/092-3. 71 records from Microzooplankton abundance measured on water bottle samples at station PS58/107-5. 63 records from Microzooplankton abundance measured on water bottle samples at station PS58/108-1. 31 records from UMMZ Mammal Collection. 15 records from Revision of southern African species of the anglerfish genus Chaunax (Lophiiformes: Chaunacidae), with descriptions of three new species. 3 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 3 records from New Zealand Arthropod Collection (NZAC). 23 records from Royal Ontario Museum - Entomology (ROME). 6697 records from Snow Petrel census, Reeve Hill, Windmill Island, East Antarctica (1984-2003). 1 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 1 records from MfN - Trace fossils. 2 records from MfN - Fossil plants (Mesophytic). 1 records from MfN - Fossil plants (Paleophytic). 71 records from Relative abundance of radiolaria in surface sediments. 9 records from ZFMK DORSA. 14 records from Coccolith percentage of surface sediment samples. 132 records from Coccolith percentage exclusive Emiliania huxleyi of surface sediment samples. 2 records from Nannofossil abundance of Hole 27-259. 194585 records from First Bird Atlas. 45 records from Nannofossil abundance of Hole 28-265. 8 records from Nannofossil abundance of Hole 28-266. 1 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 15142 records from UCT: South Africa Seaweeds(1905-2008). 2 records from Nannofossil abundance of Hole 25-249. 3 records from Coleoptera. 7 records from Nannofossil abundance of Hole 27-259. 80 records from SBMNH Vertebrate Zoology. 17847 records from Bolus Herbarium Specimens Collection (1865-2009). 9 records from Nannofossil abundance of Hole 26-250. 22 records from Nannofossil abundance of Hole 26-250A. 27 records from Nannofossil abundance of Hole 26-251. 41 records from Nannofossil abundance of Hole 26-251A. 46 records from Nannofossil abundance of Hole 26-254. 9 records from Nannofossil abundance of Hole 26-255. 14 records from Nannofossil abundance of Hole 26-258. 15 records from Diatom abundance measured on water bottle samples at station PS58/009-2. 5 records from Diatom abundance measured on water bottle samples at station PS58/108-1. 7 records from Diatom abundance measured on water bottle samples at station PS58/107-5. 11 records from Diatom abundance measured on water bottle samples at station PS58/092-3. 15 records from Diatom abundance measured on water bottle samples at station PS58/090-4. 16 records from Diatom abundance measured on water bottle samples at station PS58/088-4. 11 records from Diatom abundance measured on water bottle samples at station PS58/061-3. 5 records from Diatom abundance measured on water bottle samples at station PS58/049-3. 9 records from Diatom abundance measured on water bottle samples at station PS58/048-3. 11 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 9 records from Diatom abundance measured on water bottle samples at station PS58/045-2. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 8 records from Diatom abundance measured on water bottle samples at station PS58/041-2. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 10 records from Diatom abundance measured on water bottle samples at station PS58/014-4. 12 records from Diatom abundance measured on water bottle samples at station PS58/012-5. 12 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 8 records from Diatom abundance measured on water bottle samples at station PS58/091-4. 5 records from Diatom abundance measured on water bottle samples at station PS58/043-2. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/009-2. 7 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/011-3. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/012-5. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/038-3. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/041-2. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/043-2. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/045-2. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/046-3. 3 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/049-3. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/061-3. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/090-4. 7 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/091-4. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/107-5. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/108-1. 11 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/009-2. 17 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/011-3. 16 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/012-5. 11 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/014-4. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/038-3. 8 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/042-2. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/043-2. 13 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/045-2. 13 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/046-3. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/048-3. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/049-3. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/061-3. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 7 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/090-4. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/091-4. 12 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/108-1. 2 records from Enigmas from the past: M’Intosh’s (1885) annelidicolous copepods from the voyage of H. M. S. Challenger. 1 records from ASE - Herbário da Universidade Federal de Sergipe. 6 records from CM Herps Collection. 818 records from Range chart of calcareous nannofossils from ODP Hole 188-1165B (Table 1). 56 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 119-744. 116 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 120-748. 72 records from MSB Parasite Collection (Arctos). 872 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 37 records from (Table 4) Percentages of planktonic foraminiferal taxa from the 214 surface-sediment samples from the South China Sea and the western Pacific. 2423 records from Northern Territory Museum and Art Gallery provider for OZCAM. 11 records from Plankton abundance measured in surface water during Polarstern cruise ANT-XX/2. 91 records from Lichen herbarium, Oslo (O). 58 records from Planktic foraminifera counts of sediment core ELT48.011-PC. 42 records from Planktic foraminifera counts of sediment core ELT48.022-PC. 53 records from Planktic foraminifera counts of sediment core ELT48.027-PC. 108 records from Planktic foraminifera counts of sediment core RC08-39. 1295 records from Planktic foraminifera counts of sediment core RC08-49. 255 records from Planktic foraminifera counts of sediment core RC09-150. 130 records from Planktic foraminifera counts of sediment core RC11-120. 213 records from Planktic foraminifera counts of sediment core RC11-121. 280 records from Planktic foraminifera counts of sediment core RC11-126. 290 records from Planktic foraminifera counts of sediment core RC11-134. 6 records from ICN - Universidad Nacional de Colombia. 297 records from Planktic foraminifera counts of sediment core RC14-7. 216 records from Planktic foraminifera counts of sediment core RC14-9. 315 records from Planktic foraminifera counts of sediment core RC17-69. 95 records from Planktic foraminifera counts of sediment core RC17-73. 326 records from Planktic foraminifera counts of sediment core V14-77. 848 records from Planktic foraminifera counts of sediment core V14-81. 71 records from Planktic foraminifera counts of sediment core V16-89. 310 records from Planktic foraminifera counts of sediment core V18-191. 201 records from (Table 2) Relative abundances of calcareous nannofossils in ODP Hole 120-748A. 5841 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 4189 records from (Table 2) Ranges of middle Eocene through Holocene planktonic foraminifera in ODP Hole 119-738C. 9660 records from (Table 3) Ranges of upper Eocene Holocene planktonic foraminifera in ODP Hole 119-744A. 480 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 64 records from (Table 2) Distribution of calcareous nannofossils in ODP Hole 119-738C. 250 records from (Appendix) Relative abundance of some calcareous nannofossils in ODP Hole 119-738C. 900 records from Occurrence of dinoflagellate cysts in ODP Hole 119-738C (Appendix). 6348 records from (Table 1) Distribution of benthic foraminifera in ODP Site 120-747. 777 records from (Table 2) Distribution of benthic foraminifera in ODP Hole 120-748A. 8216 records from (Table 4) Distribution of benthic foraminifera in ODP Site 120-750. 103 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 1610 records from (Appendix A) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747A. 1530 records from (Appendix B) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747C. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 945 records from (Appendix D) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748C. 1850 records from (Appendix E) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749B. 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 983 records from (Table 2) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-747A. 1336 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 287 records from (Table 3) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-749B. 536 records from (Table 1) Absolute abundances of benthic foraminifera in ODP Site 120-747. 1039 records from (Table 3) Relative abundances of benthic foraminifera in ODP Site 120-748. 473 records from (Table 3) Relative abundances of benthic foraminifera in ODP Site 120-747. 1158 records from (Table 2) Absolute abundances of benthic foraminifera in ODP Site 120-748. 2553 records from (Appendix A) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-747A. 2349 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 2750 records from (Appendix C) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-751A. 890 records from RMT Trawl catch from the 2005/06 V3 BROKE-West voyage - Zooplankton. 2629 records from LACM Vertebrate Collection. 7 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 2 records from Natural History Museum Rotterdam (NL) - Chordata collection. 1 records from Colección Nacional de Equinodermos Mexicanos (ICMyL-DF, UNAM). 16 records from Collection Crustacea ZMG. 6 records from Insecta ZMK. 403 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 3686 records from SOMBASE BIOCONSTRUCTORS. 1 records from TRTE Herbarium (TRTE). 62883 records from IZIKO South Africa Museum Collection (1800-2013). 222 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 628 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 268 records from Biogeographic distribution of the Antarctic and Sub-Antarctic brachiopods (living forms). 336 records from Biogeographic distribution of Antarctic and sub-Antarctic Cumacea. 2004 records from Antarctic Jellyfish. 97 records from Biogeographic distribution of Antarctic and sub-Antarctic Mysida. 42 records from Marine birds and mammals of the Southern Ocean (a census for the CAML). 1 records from Bacteria from Penguin Guano, Antarctica. 4 records from Mitochondrial lineages in the Antarctic sea slug Doris kerguelenensis. 2 records from Antarctic Foraminiferans. 3 records from Penguins of Antarctica. 883 records from Asteroids from French subantarctic islands: records from the Marion Dufresne MD03 expeditions. 201 records from SO-Polylist. 9 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 1 records from In situ observations of Stygiomedusa gigantea. 8 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 927 records from RMT Trawl catch from the 1982/83 V2 ADBEX I voyage. 138 records from RMT Trawl catch from the 1983/84 V5 ADBEX II voyage. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 1212 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 10 records from Collection Bryozoa - ZIM Hamburg. 6 records from Collection Crustacea - ZIM Hamburg. 43 records from Collection Hydrozoa - ZSM München. 51 records from Collection Bryozoa - ZMB. 21 records from Collection Cnidaria - ZMB. 293 records from Collection Crustacea - ZMB. 70 records from Collection Echinodermata - ZMB. 25 records from Collection Hydrozoa - ZMB. 107 records from Collection Porifera - ZMB. 85 records from Collection Vermes - ZMB. 69 records from The Fungal Collection at the Botanische Staatssammlung München. 177 records from Ant'Phipoda Database (New records). 103453 records from ANTAVIA-TrackingKing. 2 records from Bush Blitz aids description of three new species and a new genus of Australian beeflies (Diptera: Bombyliidae: Exoprosopini). 1700 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 1 records from The Mammalia Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 264 records from The Lichen Collection at the Botanische Staatssammlung München. 4 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 1 records from Estación Experimental de Zonas Áridas (CSIC) EEZA - Aves. 2 records from Natural History Museum Rotterdam (NL) - Invertebrata miscellaneous Collection. 3847 records from Tropicos Specimen Data. 242 records from British Antarctic Survey Argos satellite tracking data. 1502 records from SOMBASE PYCNOGONIDS. 9 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-7. 13 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-9. 26 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 1222 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 181077 records from Western Australian Museum provider for OZCAM. 12 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 282 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 113 records from Survey of benthic and other marine invertebrates of Prydz Bay, 1990/91 Voyage 6. 120 records from (Table 3) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-754A. 1152 records from (Table 1) Occurrence of Oligocene to Pleistocene benthic foraminifers in ODP Hole 121-754A. 360 records from (Figure 6) Range chart of planktonic foraminifers across the K/T boundary at ODP Hole 120-750A. 140 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 348 records from (Table 2) Distribution of planktonic foraminifera in ODP Hole 183-1136A. 240 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part I. 615 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part I. 410 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part II. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-13. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 10 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-14. 13 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 15 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 46 records from Squid collection from 1995/96 V4 BROKE. 352 records from SysTax - Zoological Collections. 2 records from The Peacock Spiders (Araneae: Salticidae: Maratus) of the Queensland Museum, including six new species. 1 records from Chaetognatha - SMF. 10 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-10. 12 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-1. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-6. 300 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part II. 2 records from Naturhistorisches Museum Mainz, Zoological Collection. 607 records from SOUTHERN OCEAN ISOPODA. 16555 records from Natural History Museum (London) Collection Specimens. 13 records from (Table 2) Dissolution index (XDX) values and average test mass for four species of planktonic foraminifera. 564 records from Natural History Museum, Vienna - Herbarium W. 228 records from Cetacean Sightings Survey and Southern Ocean Cetacean Program - BROKE-West. 672 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 332 records from Macaulay Library Audio and Video Collection. 107 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 18 records from Harold W. Manter Laboratory of Parasitology Collection. 1 records from Tartu University, palaeontology collections. 159 records from (Table 1) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Site 120-747. 1634 records from (Table 2) Stratigraphic occurrences of the dinoflagellate cysts in lithologic Subunit IIIB of ODP Hole 120-748C. 116 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 6290 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 1674 records from (Table 3) Neogene benthic foraminifers of ODP Hole 120-751A. 1239 records from (Table 1) Neogene benthic foraminifers of ODP Hole 120-747A. 515 records from (Table 2) Neogene benthic foraminifers of ODP Hole 120-748B. 114 records from Abundances of shells of planktic foraminifera species in Upper Miocene sediments from the Indian Ocean and relative abundances of their groups. 2279 records from (Table 1) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-752A. 2 records from Apectodinium spp. and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 182-1128D. 2 records from Field Museum of Natural History (Botany) Fungi Collection. 245 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 426 records from (Table 3) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Site 120-750. 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 10800 records from NMNH Extant Specimen and Observation Records. 10251 records from ARC-PPRI: National Survey of Arachnida (1905-2009). 156 records from (4) Assemblages of planktic foraminifera and Sea Surface Temperature (SST) reconstructed from the Modern Analogue Technique in sediment core MD02-2488 during the Last Interglacial. 186 records from (3) Sea Surface Temperature (SST) reconstructed from the percentage of Neogloboquadrina pachyderma sinistral in sediment core MD02-2488 during the period 50-140 ka. 216 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from Collection Onychophora - SMF. 1 records from Collection Ornithologie - SNSD. 1 records from Collection Soil Aninmals. 26 records from Edaphobase. 60 records from Partial Amphibians Collection. 2 records from Swiss Psyllid (Hemiptera) Collections - Basel. 40 records from Parasitic Platyhelminthes Collections. 2821 records from SOMBASE. 3260 records from ANTARCTIC PLANT DATABASE. 219 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 59548 records from Seabirds of the Southern and South Indian Ocean. 4595 records from Weddell Seal census, Vestfold Hills, Antarctica. 20992 records from Weddell Seal Sightings, Vestfold Hills, Antarctica. 1794 records from Elephant Seal Sightings, Heard Island. 5260 records from Whale catches in the Southern Ocean. 4793 records from Australian Antarctic Division Herbarium. 215708 records from ARGOS Satellite Tracking of animals. 97 records from National Whale and Dolphin Sightings and Strandings Database. 75600 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 931 records from Cetacean Sightings Survey and Southern Ocean cetacean program. 8193 records from APIS - Antarctic Pack Ice Seals 1994-1999, plus historical data from the 1980's. 924 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 5 records from Canadian Museum of Nature Herbarium. 5 records from UWBM Mammalogy Collection. 704 records from UWBM Ornithology Collection. 4 records from UWFC Ichthyology Collection. 5 records from UF Florida Museum of Natural History Mammals. 6 records from University of Florida Herpetology. 36 records from Real Jardin Botanico, Madrid: MA-Musci. 10 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 637 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 2 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 191 records from Institut Botanic de Barcelona, BC. 3 records from HMAP-History pf Marine Animal Populations (CoML). 17815 records from NODC WOD01 Plankton Database. 968 records from SeamountsOnline (seamount biota) (CoML). 2222 records from Natural Geography In Shore Areas (NaGISA) Dataset. 11 records from Bishop Museum Data (OBIS distribution) (USOBIS). 54 records from Generic Taxonomic Database System on Mysida and Nematoda. 467 records from Academy of Natural Sciences OBIS Mollusc Database. 14453 records from SEAMAP - marine mammals, birds and turtles. 1665 records from Hexacoral Database. 9 records from Atlantic Reference Centre (OBIS Canada). 2 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 116 records from AIMS - Bioresources Library (OBIS Australia). 14407 records from Natal Museum - Mollusc Collection (AfrOBIS). 5004 records from iziko South African Museum - Fish Collection (AfrOBIS). 174 records from iziko South African Museum - Marine Mammal Collection (AfrOBIS). 79 records from Marine and Coastal Management - Seal Surveys (AfrOBIS). 31700 records from Marine and Coastal Management - Copepod Surveys (AfrOBIS). 4998 records from iziko South African Museum - Shark Collection (AfrOBIS). 5399 records from Bolus Herbarium Algal Specimen Database (AfrOBIS). 3156 records from iziko South African Museum - Mollusc Collection (AfrOBIS). 2 records from Cetacean distribution in the South Atlantic and South Pacific Ocean (AR-OBIS). 416 records from Marine and Coastal Management - Demersal Surveys (years 1983-1985) (AfrOBIS). 21209 records from Marine and Coastal Management - Demersal Surveys (years 1986-1990) (AfrOBIS). 48452 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 9512 records from Marine and Coastal Management - Demersal Surveys (years 1996-2000) (AfrOBIS). 12649 records from Marine and Coastal Management - Demersal Surveys (years 2001-2005) (AfrOBIS). 2326 records from Marine and Coastal Management - Demersal Surveys (years 2006-) (AfrOBIS). 23196 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 30863 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1985) (AfrOBIS). 43737 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1986) (AfrOBIS). 42186 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1986) (AfrOBIS). 47246 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1987) (AfrOBIS). 39404 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1987) (AfrOBIS). 12 records from MICROBIS database. 42244 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1988) (AfrOBIS). 41504 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1988) (AfrOBIS). 52841 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1989) (AfrOBIS). 42284 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1989) (AfrOBIS). 52804 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2000) (AfrOBIS). 39443 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2000) (AfrOBIS). 44570 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2001) (AfrOBIS). 28299 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2001) (AfrOBIS). 25548 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2002) (AfrOBIS). 26157 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2002) (AfrOBIS). 25884 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2003) (AfrOBIS). 19529 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2003) (AfrOBIS). 29843 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2004) (AfrOBIS). 27396 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2004) (AfrOBIS). 28126 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2005) (AfrOBIS). 19793 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2005) (AfrOBIS). 54060 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1999) (AfrOBIS). 41079 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 51725 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1998) (AfrOBIS). 44938 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1998) (AfrOBIS). 46893 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1995) (AfrOBIS). 41447 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 50954 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1996) (AfrOBIS). 39787 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1996) (AfrOBIS). 46759 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1997) (AfrOBIS). 39920 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1997) (AfrOBIS). 129 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 63 records from Michigan State University Herbarium Lichens. 9 records from LSUMZ Mammals Collection. 4648 records from Paleobiology Database. 12 records from Fish collection of National Museum of Nature and Science. 207 records from Individual Sightings. 1235 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 3 records from SDNHM Birds Collection. 147 records from Arizona State University Lichen Collection. 185 records from Galathea II, Danish Deep Sea Expedition 1950-52. 471 records from Western Palearctic migratory birds in continental Africa. 2 records from The University of Hong Kong Herbarium. 1 records from DAV UC Davis Center for Plant Diversity. 6 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 23 records from MEXU/Colección de Briofitas. 2 records from Plants of Papua New Guinea. 4 records from Mammal specimens. 9 records from MMNH Museum Bird Collection. 23 records from Invertebrate Paleontology Division, Yale Peabody Museum. 1355 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 3 records from Invertebrate Zoology Division, Yale Peabody Museum. 5 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 54 records from TTU Mammals Collection. 54 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 2 records from Algaterra Types. 30 records from Herbarium Berolinense. 107 records from Lichen Herbarium Berlin. 60 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 20 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 445 records from Biologiezentrum Linz. 78 records from United States National Plant Germplasm System Collection. 462 records from The System-wide Information Network for Genetic Resources (SINGER). 32 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 2 records from The Erysiphales Collection at the University Halle-Wittenberg. 41 records from IndOBIS, Indian Ocean Node of OBIS. 2 records from Nordic Genetic Resources. 4 records from USU-UTC Specimen Database. 722 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 36298 records from Pelagic Fish Observations 1968-1999. 174 records from UF Invertebrate Zoology. 3 records from The Collection of Fungi of the Real Jardín Botánico of Madrid (MA-Fungi). 53 records from Fish Collection of Natural History Museum and Institute, Chiba. 197 records from HBGSpermatophyta - Herbarium Hamburgense. 1 records from The Myxomycetes Collection at the V. L. Komarov Botanical Institute, St. Petersburg. 3 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 403 records from Inventory of Antarctic seabird breeding sites. 980 records from Electron Micrograph Database - Marine Specimens. 141 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 43 records from Kelp rafts in the Southern Ocean. 53730 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1990) (AfrOBIS). 45775 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1990) (AfrOBIS). 55929 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1991) (AfrOBIS). 47540 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1991) (AfrOBIS). 49974 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1992) (AfrOBIS). 51743 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1992) (AfrOBIS). 56353 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1993) (AfrOBIS). 45384 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1993) (AfrOBIS). 46125 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1994) (AfrOBIS). 39853 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1994) (AfrOBIS). 4 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 50 records from Harvard University Herbaria. 1 records from UCLA Donald R. Dickey Bird and Mammal Collection. 20 records from DSMZ Prokarya Collection Catalogue. 2233 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage. 514 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage. 1973 records from RMT Trawl catch from the 1995/96 V4 BROKE voyage. 359 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 18 records from EURISCO, The European Genetic Resources Search Catalogue. 979 records from Electron Micrograph Database (Australian Antarctic Data Centre). 14856 records from Pelagic Fish Observations 1968-1999 (Australian Antarctic Data Centre). 43 records from Kelp rafts in the Southern Ocean (Australian Antarctic Data Centre). 1 records from New South African species of the genus Idiasta Foerster, 1863 (Hymenoptera: Braconidae: Alysiinae), with a key to the Afrotropical and Malagasy taxa. 359 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82 (Australian Antarctic Data Centre). 942 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage (Australian Antarctic Data Centre). 4230 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage (Australian Antarctic Data Centre). 3608 records from MAL. 603 records from Diatoms from the Vestfold Hills Lakes. 1883 records from AAD Benthic Sampling Database. 1599 records from Planktic foraminifera assemblage of sediment core ELT45.029-PC. 1792 records from Planktic foraminifera assemblage of sediment core ELT49.017-PC. 2320 records from Planktic foraminifera assemblage of sediment core ELT49.018-PC. 2115 records from Planktic foraminifera assemblage of sediment core ELT49.021-PC. 755 records from Planktic foraminifera assemblage of sediment core ELT49.023-PC. 6862 records from Planktic foraminifera counts in surface sediment samples. 96 records from Distribution of planktonic foraminifera in surface sediment samples A180-072 to V23-83. 194 records from (Table 2) Sea surface temperature reconstruction from sediment core MD88-770. 191 records from Modern planktic foraminifera assemblage from surface sediment samples used as reference data set for the reconstruction of Atlantic sea surface temperatures during the last glacial maximum (LGM). 2348 records from Composition of planktonic foraminifera species in 1123 surface sediment samples compared with sea surface temperatures from the Levitus Atlas. 656 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 76 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947). 4554 records from Planktic foraminifera counts (census) of sediment core MD96-2080. 518 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-120. 772 records from Relative abundance of planktic foraminifera in sediment core RC08-39. 1073 records from Relative abundance of planktic foraminifera in sediment core RC17-69. 2 records from WNMU Mammal Collection (Arctos). 465 records from Naturalis Biodiversity Center (NL) - Aves. 547 records from RMT Trawl catch from the 2005/06 V3 BROKE-West voyage - Fish. 408 records from Moss sampling in the Windmill Islands and the Vestfold Hills. 359 records from Mosquito Occurrence Dataset. 262 records from Antarctic Echinoids: an interactive database. 20720 records from CCAMLR historic KRILL. 40 records from Taxonomic revision of the spider family Penestomidae (Araneae, Entelegynae). 82 records from Antarctic Krill occurrence data from Discovery expeditions. 3 records from Antarctic Krill occurrence data from Japanese expeditions. 233 records from Antarctic Krill occurrence data from Australian expeditions. 1009 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 479 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 1221 records from Collections data on ecology of bottom animal of the Southern ocean. 107 records from Nemertina World Checklist. 212 records from Christopher Walker collection of Glomeromycotan fungi. 302 records from Invertebrates compiled by W.Block. 74 records from (Appendix B) Coiling ratios of Globorotalia zealandica and Globorotalia praescitula plexi from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 856 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 316 records from Moss species from Heard Island, 1987 and 2000. 884 records from Invertebrate survey, Heard Island 2001. 22 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 71 records from Field Museum of Natural History (Botany) Bryophyte Collection. 544 records from (Table AT6) Planktonic foraminiferal stratigraphy of ODP Hole 182-1130B. 440 records from CSIRO, Cruise SS199101, Marine Biology Data, Western Australia, 1991. 25 records from Phytoplankton abundance in surface water during Akademik Vernadsky cruise AV24. 60 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 98 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 2 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 29520 records from (Table T2) Foraminifer distribution in ODP Site 188-1165 sediments. 61 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 133 records from Relative abundance of organic-walled dinoflagellate cysts in surface sediments. 113 records from Planktic foraminifera abundance of Hole 26-250. 138 records from Planktic foraminifera abundance of Hole 26-250A. 373 records from Planktic foraminifera abundance of Hole 26-251. 963 records from Planktic foraminifera abundance of Hole 26-251A. 3988 records from Planktic foraminifera abundance of Hole 26-254. 186 records from Planktic foraminifera abundance of Hole 26-255. 410 records from Planktic foraminifera abundance of Hole 26-258. 2029 records from Planktic foraminifera abundance of Hole 26-258A. 1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments. 447 records from Occurrence of 13 crabeater seals (Lobodon carcinophaga) from ARGOS satellite track observations during campaign DRE1998. 100 records from Planktic foraminifera abundance of Hole 28-264. 182 records from Planktic foraminifera abundance of Hole 28-264A. 104 records from Planktic foraminifera abundance of Hole 28-265. 59 records from Planktic foraminifera abundance of Hole 28-266. 2 records from Planktic foraminifera abundance of Hole 28-267. 31 records from Planktic foraminifera abundance of Hole 28-264. 85 records from Planktic foraminifera abundance of Hole 28-264A. 39 records from Planktic foraminifera abundance of Hole 28-265. 22 records from Planktic foraminifera abundance of Hole 27-259. 21 records from KUBI Ichthyology Collection. 113 records from Natural History Museum, University of Tartu. 80 records from University of British Columbia Herbarium (UBC) - Algae Collection. 2 records from MLZ Bird Collection (Arctos). 2 records from Herbarium of Umeå University (UME). 2986505 records from Southern African Bird Atlas Project 2: Full protocol records. 165 records from Field Museum of Natural History (Botany) Seed Plant Collection. 10 records from Range table from planktonic foraminifers in ODP Hole 182-1126A. 349 records from Range table from planktonic foraminifers in ODP Hole 182-1126B. 269 records from Range table from planktonic foraminifers in ODP Hole 182-1126C. 96 records from Range table from planktonic foraminifers in ODP Hole 182-1126D. 22 records from Range table from planktonic foraminifers in ODP Hole 182-1127A. 542 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 18 records from Range table from planktonic foraminifers in ODP Hole 182-1128A. 184 records from Range table from planktonic foraminifers in ODP Hole 182-1128B. 1 records from MPM Milwaukee Public Museum Herbarium. 194 records from Range table from planktonic foraminifers in ODP Hole 182-1128C. 10 records from Range table from planktonic foraminifers in ODP Hole 182-1128D. 11 records from Range table from planktonic foraminifers in ODP Hole 182-1129A. 14 records from Range table from planktonic foraminifers in ODP Hole 182-1129B. 273 records from Range table from planktonic foraminifers in ODP Hole 182-1129C. 140 records from Range table from planktonic foraminifers in ODP Hole 182-1129D. 429 records from Range table from planktonic foraminifers in ODP Hole 182-1130A. 295 records from Range table from planktonic foraminifers in ODP Hole 182-1130B. 45 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 498 records from Range table from planktonic foraminifers in ODP Hole 182-1131A. 102 records from Range table from planktonic foraminifers in ODP Hole 182-1131B. 289 records from Range table from planktonic foraminifers in ODP Hole 182-1132B. 110 records from Range table from planktonic foraminifers in ODP Hole 182-1132C. 12 records from Range table from planktonic foraminifers in ODP Hole 182-1133A. 97 records from Range table from planktonic foraminifers in ODP Hole 182-1133B. 59 records from Range table from planktonic foraminifers in ODP Hole 182-1133C. 387 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 12 records from Range table from planktonic foraminifers in ODP Hole 182-1134B. 21 records from Range table from planktonic foraminifers in ODP Hole 183-1135A. 5 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 4 records from Range table from planktonic foraminifers in ODP Hole 183-1137A. 16 records from Range table from planktonic foraminifers in ODP Hole 183-1138A. 38 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 3 records from Range table from planktonic foraminifers in ODP Hole 183-1141A. 944 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 4 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 87 records from Range table from benthic foraminifers in ODP Hole 182-1131A. 1 records from Range table from benthic foraminifers in ODP Hole 188-1165A. 91 records from Range table from benthic foraminifers in ODP Hole 188-1165B. 8 records from Range table from benthic foraminifers in ODP Hole 188-1165C. 7 records from Colección Nacional de Herpetología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 284 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 117 records from Range table from benthic foraminifers in ODP Hole 182-1126D. 182 records from Range table from benthic foraminifers in ODP Hole 182-1128B. 60 records from Range table from benthic foraminifers in ODP Hole 182-1128C. 37 records from Range table from benthic foraminifers in ODP Hole 182-1128D. 226 records from Range table from benthic foraminifers in ODP Hole 182-1130A. 273 records from Range table from benthic foraminifers in ODP Hole 182-1132B. 133 records from Range table from benthic foraminifers in ODP Hole 182-1134A. 516 records from Occurence of microfossils in Early Cretaceous sediments of DSDP Hole 25-249 (Tab. 1). 2291 records from (Table 3) Distribution of benthic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 93 records from CSIRO, Australian National Algae Culture Collection, Global, 1949-2008. 20 records from Diversity of total live benthic foraminiferal assemblages in South Atlantic surface sediments. 52 records from Diversity of live benthic foraminiferal assemblages in South Atlantic surface sediments. 72 records from Diversity of dead benthic foraminiferal assemblages in South Atlantic surface sediments. 1685 records from Dead benthic foraminifera in South Atlantic surface sediments. 301 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 249 records from (Table 3) Distribution of benthic foraminifers in middle Miocene sediments of ODP Hole 182-1126B in the Great Australian Bight. 142 records from (Table 3) Distribution of benthic foraminifers in middle Miocene sediments of ODP Hole 182-1134A in the Great Australian Bight. 3 records from R. L. McGregor Herbarium Lichen Collection. 13361 records from ABBBS Bird Banding records from the Australian Antarctic Territory and Heard Island.. 534 records from Leopard Seal census, Heard Island 1987/88. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 11 records from Subantarctic Fur sealsat Heard Island, 1987/88. 129 records from Squid specimens from the 1991/92 V6 AAMBER2 voyage. 267 records from Senckenberg - CeDAMar Resource. 493 records from Texas A&M University Insect Collection. 1 records from UAZ Mammals. 1360 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 792 records from COMARGIS: Information System on Continental Margin Ecosystems. 43 records from Entomology Division, Yale Peabody Museum. 1 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 3 records from Paleobotany Division, Yale Peabody Museum. 18 records from DBL_Life. 140 records from Bunger Hills, 1999/2000 survey - nest sites of snow petrels Pagodroma nivea. 117 records from Whale Observations from the British, Australian and New Zealand Antarctic Research Expedition (BANZARE) voyages 1929-30 and 1930-31. 5056 records from Nest census, Windmill Islands 2002/03. 145 records from Whale log - observations from ANARE voyages. 6555 records from BIOLOGICAL SCIENCES DATA. 1 records from KTP Ring Data. 6 records from Collection Pisces SMF. 40 records from Collection Arachnology SMF. 15 records from Collection Porifera SMF. 1 records from Collection Mollusca SMF. 20 records from Collection Polychaeta SMF. 6 records from Collection Aves (spirit preserved) SMF. 41 records from Collection Cnidaria SMF. 23 records from Herbarium Senckenbergianum (FR). 12 records from Collection Aves (bird skins) SMF. 24 records from Collection Crustacea SMF. 1 records from Collection Bryozoa SMF. 1 records from Collection Tunicata SMF. 4 records from Collection Tardigrada SMF. 3 records from Collection Echinodermata SMF. 421 records from SINGER Coordinator. 27 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 55 records from Type Localities for organisms and fossils first described from Antarctica. 121 records from Southern Giant Petrel census data within the Australian Antarctic Territory.. 5588 records from Snow Petrel nest census, Mawson region 2004/05. 845 records from Diatom and foraminiferal samples from surficial sediments of Prydz Bay, Antarctica. 203 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 1 records from Database of Native Plants in Taiwan. 463 records from AMNH Bird Collection. 374 records from AMNH Mammal Collections. 942 records from Ophiuroidea collections of the Zoological Institute Russian Academy of Sciences. 15 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 1 records from (Table 1) King penguins' (Aptenodytes patagonicus) path characteristics to their colony, Kerguelen Island. 6224 records from Ditsong National Museum of Natural History Collection: 1805-2008. 14 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 14 records from Molecular and morphological characterisation of new species in the trapdoor spider genus Aname (Araneae: Mygalomorphae: Nemesiidae) from the Pilbara bioregion of Western Australia. 37 records from SMNS Herpetologie. 58 records from MVZ Egg and Nest Collection (Arctos). 8063 records from (Appendix B1) Relative abundances of middle Eocene-late Oligocene calcareous nannofossils in ODP Hole 120-748B. 297 records from Circumpolar dataset of sequenced specimens of Promachocrinus kerguelensis (Echinodermata, Crinoidea). 2 records from (Table 4) Differences in king penguin (Aptenodytes patagonicus) colony arrivals and departures based on age, Possession Island. 1 records from Revision of the genus Euthalenessa Darboux (Polychaeta: Sigalionidae). 2 records from A new species of Anacaena Thomson, 1859 from South Africa (Coleoptera: Hydrophilidae). 61 records from Naturalis Biodiversity Center (NL) - Porifera. 3 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 5 records from Collection ornithologique A. Maës. 4008 records from Queensland Museum provider for OZCAM. 2796 records from ARC-PPRI: Collection of Southern African bees (1800-2007). 5057 records from Bureau of Rural Sciences, Commercial Fisheries Presence, Australia, 2000-2002. 2 records from CUMV Amphibian Collection (Arctos). 14701 records from NMSA: Arthropod Collections (1900-2012). 5641 records from Lund Botanical Museum (LD). 292 records from (Table AT2) Planktonic foraminiferal stratigraphy of ODP Hole 182-1126C. 71 records from Auckland Museum Land Vertebrates Collection. 73 records from Snow Entomological Museum Collection. 6 records from Spider Mites Collection of Jean Gutierrez. 8100 records from Geographically tagged INSDC sequences. 2 records from Ouellet-Robert entomological collection (QMOR). 131 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Hole 182-1127B. 1 records from On a new species of the rare syllid genus Exogonoides (Annelida, Phyllodocida, Syllidae). 21 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 102 records from Field Museum of Natural History (Zoology) Fish Collection. 14 records from MSB Mammal Collection (Arctos). 14 records from MSB Host Collection (Arctos). 1 records from Ghent university - Zoology Museum - Nematod Collection. 2249 records from Royal Museum of Central Africa - True Fruit Flies (Diptera, Tephritidae) of the Afrotropical Region (ENBI wp13). 232 records from Geographic distribution of dinoflagellate cysts in surface sediments. 657 records from SANBI: Rare and Threatened Plants (Cape Floristic Region, 1864-2008). 2461 records from ARC-PPRI: Chalcidoidea Collection (1900-2010). 11 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 1080457 records from SAFRING: Historical Bird Ringing Records (2005-2009). 2730 records from (Table AT5) Planktonic foraminiferal stratigraphy of ODP Hole 182-1130A. 564 records from The echinoderm collection (IE) of the Muséum national d'Histoire naturelle (MNHN - Paris). 474 records from The cnidarians collection (IK) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2512 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 32 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 1 records from University of Tennessee at Chattanooga. 11 records from (Table T6) Relative abundance of Cretaceous plant microfossil taxa of ODP Site 188-1166. 1652 records from NU: KwaZulu-Natal Invasive Alien Species (1821-2011). 2 records from The Fish Database of Taiwan. 54 records from Animal Sound Archive. 2847 records from (Table AT1) Planktonic foraminiferal stratigraphy of ODP Hole 182-1126B. 90 records from Bernice P. Bishop Museum. 72543 records from DNSM: Durban Natural Science Museum Insect Collection (1900-2011). 145 records from CUMV Reptile Collection (Arctos). 19459 records from EWT: African Crane Conservation Programme Sightings. 205 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Cowan Tetrapod Collection - Birds. 1 records from Carnet en Ligne. 60 records from (Table T1) Diatom biostratigraphy of ODP Hole 183-1140A. 682 records from UMMZ Birds Collection. 13923 records from Australian National Insect Collection. 102 records from Royal Botanic Garden Edinburgh Herbarium (E). 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 221 records from Botany (UPS). 2369 records from European Molecular Biology Laboratory Australian Mirror. 37 records from DMNH Birds. 35 records from Instituto de Ciencias Naturales. 2542 records from ARC-PPRI: National Collection Of Fungi(1817-2009). 172 records from Mammalogy Collection - Royal Ontario Museum. 62 records from NMNH Paleobiology Specimen Records. 215 records from MSB Bird Collection (Arctos). 2511 records from UCT: Southern African Reptile Conservation Assessment (1910-2009). 86 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 3 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 3 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 2109 records from University Of Pretoria: Lacewing Database Project (1911-2015). 2599 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1888 records from CAS Herpetology (HERP). 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 385 records from Queen Victoria Museum Art Gallery provider for OZCAM. 3 records from A new species of Lygistorrhina Skuse (Diptera: Sciaroidea: Lygistorrhinidae) from South Africa. 15 records from (Table 1) Mean body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 563 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 58 records from Hymenoptera. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 8 records from Global compendium of Aedes aegypti occurrence. 342 records from (Table AT9) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134B. 10 records from Natural History Museum Rotterdam (NL) - Insecta collection. 1 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 8 records from The French Collection of Medicago truncatula. 4 records from NCSM Invertebrates Collection. 5 records from UB - Herbário da Universidade de Brasília. 29 records from Naturalis Biodiversity Center (NL) - Mollusca. 2291 records from Catalogue of Afrotropical Bees. 292 records from The crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 14 records from KUBI Herpetology Collection. 44230 records from Australian Museum provider for OZCAM. 2 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 1 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 3131 records from University of Pretoria: Dung Beetles (Coleoptera: Scarabaeidae: Scarabaeinae). 112 records from Allan Herbarium (CHR). 4 records from Entomology at ZMUC, Natural History Musem of Denmark. 11 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 68 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 2 records from Revision of African Apiocera (Diptera: Apioceridae). 38327 records from Neptune Deep-Sea Microfossil Occurrence Database. 3 records from Auckland Museum NZ Marine Collection. 4 records from A new species of Stasimopus from the Eastern Cape Province of South Africa (Araneae, Mygalomorphae, Ctenizidae), with notes on its natural history. 51 records from MVZ Bird Collection (Arctos). 41 records from Vascular Plant Herbarium, Oslo (O). 8 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 84 records from (Table T4) Abundance of foraminifers and presence of other fragments in ODP Hole 188-1166A sediments. 1873 records from African Plants - a photo guide. 89 records from KUBI Ornithology Collection. 13 records from Anymals+plants - Citizen Science Data. 10 records from The African species of the subfamily Penestominae (Araneae: Eresidae): with descriptions of two new species. 2580 records from CSIRO, fish surveys by the Courageous, 1978-1979. 1 records from UAIC Ichthyological Collection. 4 records from NCSM Mammals Collection. 1 records from A spectacular new species of seadragon (Syngnathidae). 14 records from UF FLMNH Ichthyology. 42 records from Auckland Museum Marine Collection. 259 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 1390 records from (Appendix 1) Calcareous nannofossils in ODP Hole 119-738B. 43 records from New Zealand Fungal and Plant Disease Collection (PDD). 13 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 141 records from (Table T3) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1138A. 10 records from The Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 40 records from (Table T1) Kerogen and organic constituents in ODP Hole 183-1138A, Kerguelen Plateau. 47 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 759 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 103 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 1 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 66 records from A review of the Australian endemic clam shrimp, Paralimnadia Sars 1896 (Crustacea: Branchiopoda: Spinicaudata). 1 records from Three new species of Microbrotula (Teleostei: Ophidiiformes: Bythitidae) from the Indo-West Pacific.. 3314 records from Geneva Herbarium – General Collection (G). 5443 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 8 records from Instituto de Botánica Darwinion. 251 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 5210 records from South Australian Museum Australia provider for OZCAM. 336 records from (Table AT4) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128C. 308 records from Lichen herbarium, UiB. 6 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 810 records from Millenium Seedbank (MSB). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences